Predictions and maps of county mean indoor radon concentrations in the mid-Atlantic states - Price, P N (Health physics (1958), 1997)
Measured surface radium content, geologic province information, information on the fraction of homes with basements and with living-area basements, and measurements from the EPA/State Residential Radon Surveys, were used in a Bayesian mixed effects regression to predict the distributions of short-term winter and annual living-area average radon concentrations by county in the mid-Atlantic states. The information provided by those explanatory variables is roughly equivalent to collecting an extra 12 observations per county, effectively doubling the amount of information in a typical county. Predicted county geometric means are subject to standard errors of 15% to 30% for typical counties, with the uncertainty in a given county depending on the number of radon measurements in the county and the amount of information about the geologic province that contains the county. After controlling for soil radium concentration and the effect of measuring in a basement vs. the first floor, typical geologic provinces are found to be associated with elevation or depression of indoor radon concentrations by 30% on average, with some provinces having effects of considerably larger magnitude.